PELATIHAN BUDIDAYA SISTEM VERTIKULTUR PADA PETANI BAWANG MERAH DI DESA BULUHARJO KABUPATEN MAGETAN - Pujiati Pujiati; Dwi Rosita Sari; Cicilia Novi Primiani; Mohammad Arfi Setiawan (JPM PAMBUDI, 2021)
Buluharjo Village, Magetan Regency is a rural area, the majority of which are horticultural crops. Shallots are one of the commodities in the region. The productivity of shallots for the last three years has decreased due to the reduction in agricultural land caused by the construction of housing projects. The decline in shallot production is caused by the lack of land and the presence of plant pests such as worms, caterpillars, fungi and bacteria. The use of high chemical fertilizers, improper selection of seeds makes the quantity and quality of shallot production not optimal. The purpose of the activity is to provide training on red onion cultivation with verticulture techniques as a solution for using narrow land. The method used is pre survey, survey, socialization and training. The activity was carried out for 6 months. The result of the activity is an increase in understanding of modern agricultural techniques, namely verticulture in the field of red onion farming. Public understanding of modern agricultural systems, and increasing the productivity of shallots. The community is very enthusiastic and actively involved in applying vertical culture techniques. The community can apply the shallot verticulture technique on narrow land.